2013
DOI: 10.1021/jp405490q
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure Formation in the Lecithin/Isooctane/Water System

Abstract: We present here for the first time a study of the self-assembled nanostructures in the lecithin/isooctane/water system by direct-imaging techniques, namely, cryogenic transmission electron microscopy (cryo-TEM) and cryogenic scanning electron microscopy (cryo-SEM). Along the dilution line [water]/[lecithin] = 5, we identified a nanostructural development with the increase of lecithin concentration. The system changes from a single reverse micellar phase, through a reverse micellar phase coexisting with a lamel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…As demonstrated by several studies, lecithin microemulsion was formed without alcohol by substituting triglyceride by mineral oil (e.g. alkane and cycloalkane) [17][18][19][20]. A transition from spherical to flexible cylindrical reverse micelles was observed upon addition of small amount of water to the lecithin microemulsion [21][22][23][24][25].…”
mentioning
confidence: 99%
“…As demonstrated by several studies, lecithin microemulsion was formed without alcohol by substituting triglyceride by mineral oil (e.g. alkane and cycloalkane) [17][18][19][20]. A transition from spherical to flexible cylindrical reverse micelles was observed upon addition of small amount of water to the lecithin microemulsion [21][22][23][24][25].…”
mentioning
confidence: 99%
“…Although slush nitrogen has a cooling rate lower than organic cryogens, the rate necessary for vitrification of organic liquids is less than that of aqueous solutions 53,56 . As a result, we have found that organic electrolytes up to at least microns thick on the surface of large samples such as coin cell battery electrodes can be vitrified by plunge freezing in slush nitrogen.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…1 In particular, phospholipids 2,3 constitute an important class of molecules to build membrane models, and have been extensively used in the study of signal transduction and transport phenomena. 4 Moreover, so self-organized structures not only serve as synthetic models to mimic biological cells, 5 but also play a key role for developing carriers in drug delivery [6][7][8] or serve as encapsulating agents in the food industry. [1][2][3]9 Such versatile applications have motivated researchers to develop different methodologies for controlling their architecture.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] From a molecular point of view, though it is established that in dispersed systems amphiphiles are mainly localized at the interface between polar and nonpolar domains, the detailed representation of their arrangement is a difficult task, especially when the interfacial region extends over lengths that are hundreds of times larger than the molecular size. 5 Highresolution techniques, such as small angle scattering, are valuable tools for probing the organization of amphiphiles at the o/w interface of emulsions [6][7][8][9] and can be used to unravel the interfacial structure.…”
Section: Introductionmentioning
confidence: 99%